A survey of the reading interests of grades three to six pupils of UP Integrated School - Somera, Patricia V. (Institute of Library Science, University of the Philippines Diliman, 1984)
The study was undertaken to identify the reading interests of grade three to six pupils of the UP Integrated School (UPIS) and determine if any significant differences in reading interests exist among different grade levels, sexes, and ability groupings.